Generic analysis of bakery service encounters in Malaysia - Yih-Long, Lau; Ting, Su Hie (John Benjamins Publishing, 2016)
The study aimed to describe the staging of service encounters in a bakery in Sarawak, Malaysia. The specific aspects studied were categories of transactions, staging of transactions, and nonverbal enactment of stages of transactions. A total of 100 interactions between Chinese vendors and Chinese, Malay, and Indigenous customers at a bakery operated by Chinese vendors in Sibu, Sarawak were observed and recorded. The analysis revealed five categories: Instant Buying, where customers bought the cakes on the spot; transactions where customers waited for the cakes to be baked; transactions where customers placed an order for the cakes; transactions where the customers picked up the cakes they had ordered; and unsuccessful sales. The four obligatory stages were Sale Request, Sale Compliance, Purchase, and Goods Handover. While all four stages could be realized nonverbally, the Purchase and Goods Handover stages in the service encounters were always performed nonverbally. The results suggest no difference in the role of nonverbal communication in service encounters with Chinese and non-Chinese customers but there are cultural differences in the staging. The Chinese vendors were more likely to omit the opening (Sale Initiation and Greeting) and closing (Purchase Closure) in their interactions with non-Chinese customers than with Chinese customers. The results suggest that service encounters in high-context cultures involving customers from other ethnic groups are more likely to be instrumental exchanges with an omission of the politeness rituals that characterize interpersonal relationships.